Osteoporosis in patients with erythropoietic protoporphyria2. (22nd November 2017) - Biewenga, M.; Matawlie, R.H.S.; Friesema, E.C.H.; Koole‐Lesuis, H.; Langeveld, M.; Wilson, J.H.P.; Langendonk, J.G.
Summary: Background: Erythropoietic protoporphyria (EPP) is a rare metabolic disease with painful photosensitivity due to protoporphyrin IX accumulation. Objectives: To evaluate bone mineral density (BMD) and known osteoporosis risk factors in patients with EPP. Methods: Patients with EPP attending the Erasmus MC outpatient clinic who had undergone BMD measurements were included. Plasma 25 hydroxy (OH) vitamin D, alkaline phosphatase, parathyroid hormone and total protoporphyrin IX levels were measured; information on lifestyle, sunlight exposure and a bone‐relevant physical exercise index [Bone Physical Activity Questionnaire (BPAQ) score] was obtained via questionnaires. BMD scores and the prevalence of osteopenia and osteoporosis in the EPP population were compared with a reference population. Results: Forty‐four patients with EPP (23 female, 21 male; mean age 37·6 years) were included. The mean SDs of the T‐scores were −1·12 for the lumbar spine and −0·82 for the femoral neck (both P < 0·001). Osteopenia was present in 36%; osteoporosis in 23%. Based on the reference population the expected prevalence was 15% and 1%, respectively. Prevalence of vitamin D deficiency was 50% (defined as a 25‐OH vitamin D level < 50 nmol L −1 ). Mean self‐reported BPAQ score was 19·4 units (reference interval 19–24). Multiple linear regression analysis showed a significant influence of vitamin D deficiency and bone‐relevant physical exercise score on BMD in patients with EPP. Conclusions: The prevalence of osteoporosis and osteopenia is greatly increased in patients with EPP. Alkaline phosphatase (related to vitamin D deficiency) and amount of weight‐bearing exercise are significantly correlated with low BMD in this population. Abstract : What's already known about this topic? Patients with erythropoietic protoporphyria (EPP) have a high prevalence of vitamin D deficiency, likely related to sun‐avoidance behaviour. What does this study add? In addition to a high prevalence of vitamin D deficiency, the prevalence of osteoporosis in patients with EPP is very high. Alkaline phosphatase levels (strongly related to vitamin D deficiency) and low bone‐relevant physical activity are the most relevant predictors for osteoporosis in patients with EPP. Plain language summary available online Respond to this article